Navigating sustainable competitive advantage: social and technological challenges and open innovation in creative economy-based traditional markets - Nurul Retno Hapsari; Ahmad Zaki; Tiara Juniar Soewardi (Journal of Enterprise and Development (JED), 2024)
Purpose — Innovation and technology introduce businesses to uncertain conditions, necessitating a focus on enhancing competitiveness. This research aims to investigate the impact of social and technological challenges, as well as open innovation, on the sustainable competitive advantage of a creative economy-based traditional market.Method — This study employs a quantitative approach by distributing questionnaires to 100 MSMEs in Yogyakarta traditional markets. The Partial Least Squares-Structural Equation Modeling (PLS-SEM) was utilized to analyze the effects.Result — The results indicate that social and technological challenges contribute to a sustainable competitive advantage. However, open innovation does not significantly influence the enhancement of a sustainable competitive advantage.Practical implications  — The study suggests that the government should support MSMEs in addressing technological disruption by offering digital training to expand their market reach.